Efficacy of botulinum toxin for treating cramps in peripheral neuropathy - Mehta, Tejas; Sommers, Richard; Govindarajan, Raghav (RRNMF Neuromuscular Journal, 2021)
AbstractIntroduction:Muscle cramps are a common occurrence in patients with peripheral neuropathy and are known to cause significant distress and decrease the quality of life. Although several drug formulations have been used in the management of cramps, there is significant variability in terms of efficacy and tolerability in patients with peripheral neuropathy. This study aims to assess the efficacy of botulinum toxin A in the management of lower limb cramps in patients with peripheral neuropathy. Methods:This retrospective chart review included a total of ten patients with peripheral neuropathy with cramps. Relevant data such as age, gender, race, pain score and cause of peripheral neuropathy were documented. Statistical analyses to compare the variables was done using the Wilcoxon Test. The pain score before the administration, at 3-month, 6 month and 9 months follow up were compared. ResultsAll patients enrolled in the study showed improvement of pain assessed by visual pain analog scale. An improvement of 1.60 (95%CI, p